Direct Seed Planting System and Giving Liquid Organic Fertilizer as A New Method to Increase Rice Yield and Growth (Oryza sativa L.) - Mohamad Ikbal Bahua; Hayatiningsih Gubali (AGRIVITA, Journal of Agricultural Science, 2020)
The transplanting system is a common method in rice cultivation, whereas the direct seed planting system combined with the application of organic fertilizer is rarely applied. This study aimed to determine the impact both the direct seed planting system and the application of liquid organic fertilizer the growth and production of rice. The research used the factorial randomized block design, direct seed planting system tested by the transplanting system and application of liquid organic fertilizer doses 25, 35, and 45 l/ha. The observed variables were plant height, number of tillers, productive tillers, panicle length, weight of 1000 rice grains, and grain yield of plots. Data were analyzed by analysis of variance with 5% LSD test. The results revealed that direct seed planting system and application of liquid organic fertilizer impact the growth and yield of rice. The application of liquid organic fertilizer a dose of 45 l/ha gave the highest influence among all observed variables. There is a correlation between the treatment of the planting system and the application of liquid organic fertilizer on the growth of the number of tillers and productive tillers. The direct seed planting system increases the yield of rice more than the transplanting system.